Doxorubicin cardiotoxicity and Camellia sinensis cardioprotection determined by speckle-tracking echocardiography - Maira Souza Oliveira Barreto; Juliana Lott Carvalho; Marcos Barrouin Melo; Ana Flávia Ribeiro Machado Michel; Marina Guimarães Ferreira; Ruthnéa Aparecida Lázaro Muzzi; Alfredo Miranda de Goes; Marilia Martins Melo (Universidade de São Paulo, 2023)
Abstract Doxorubicin (Dox) is a medication used in the treatment of cancerous tumors and hematologic malignancies with potentially serious side effects, including the risk of cardiotoxicity. Flavonoids are plant metabolites with antioxidant properties and can be extracted from Camellia sinensis (CS). The aim of this study is to evaluate the possible cardioprotective effect of CS against injuries induced by Dox in rats. A total of 32 animals were distributed into four groups: (1) control - intraperitoneal injection (I.P.) of 0.5 mL saline weekly and 1.0 mL water by gavage daily; (2) CS - 0.5 mL saline I.P. weekly and 200 mg/kg CS by gavage daily; (3) Dox - 5.0 mg/kg Dox I.P. weekly and 1.0 mL water by gavage daily; and (4) Dox+CS -5.0 mg/kg Dox I.P. weekly and 200 mg/kg CS by gavage daily. Clinical examinations, blood profiles, electrocardiograms, echocardiograms, and histological analyses of hearts were performed over 25 days. The animals in the Dox group showed changes in body weight and in erythrogram, leukogram, electrocardiography, and echocardiography readings. However, animals from the dox+CS group had significantly less change in body weight, improved cardiac function, and showed more preserved cardiac tissue. This study demonstrated that CS prevents dox-induced cardiotoxicity, despite enhancing the cytotoxic effect on blood cells.